Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV METEOR during cruise M73/1 - Frank Strozyk; Jan F Metzen; Sebastian Krastel; Volkhard Spieß; Achim J Kopf (PANGAEA, 2025)
Raw multibeam bathymetry data were collected using the ship extquotesingles own SIMRAD EM120 multibeam echosounder during the RV METEOR cruise M73/1 WestMed. The cruise took place between 2007-07-21 and 2007-08-12 (Cadiz, Spain – Genoa, Italy). During leg M73/1, transit data were collected in the EEZ of Spain. In the EEZ of France, data were recorded to map the study area along western Ligurian Margin, covering water depths from 10 to 2500 m. Multibeam mapping, ROV surveys and in situ CPTu (cone penetration tests with pore pressure) deployments revealed active present-day deformation. The results were used in an IODP drilling proposal and various manuscripts. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).